1995
DOI: 10.1103/physrevlett.75.1194
|View full text |Cite
|
Sign up to set email alerts
|

Low-Energy Excitations and the Electronic Specific Heat of YbBiPt

Abstract: Neutron scattering data from the cubic heavy-fermion compound YbBiPt are presented, along with an interpretation in terms of strongly broadened crystal-field levels. To first order, the ground state is sixfold degenerate, consisting of a doublet (17) and quartet (I' s). Integration over these levels reproduces the observed linear specific-heat coefficient y of 8 Jmol ' K to within~20%. At the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…20 On the other hand, inelastic neutron scattering experiments found a scattering peak at E = 5.7 meV, which was identified as a CEF level transition to an excited doublet, and two inelastic peaks centered at ≈ 1 and 2 meV, which become resolved at T 10 K and lie on top of two broad quasielastic signals. 7 Experiments have not yet detected any dispersion associated with the peaks at ≈ 1 and 2 meV, which suggests that they may correspond to CEF level transitions. As for the broad quasielastic signals, they are also seen above 10 K, and it has been proposed that they arise from transitions occurring within the Γ 7 doublet and Γ 8 quartet.…”
Section: B Thermal Expansion and The Crystalline-electric-field Schemementioning
confidence: 99%
See 4 more Smart Citations
“…20 On the other hand, inelastic neutron scattering experiments found a scattering peak at E = 5.7 meV, which was identified as a CEF level transition to an excited doublet, and two inelastic peaks centered at ≈ 1 and 2 meV, which become resolved at T 10 K and lie on top of two broad quasielastic signals. 7 Experiments have not yet detected any dispersion associated with the peaks at ≈ 1 and 2 meV, which suggests that they may correspond to CEF level transitions. As for the broad quasielastic signals, they are also seen above 10 K, and it has been proposed that they arise from transitions occurring within the Γ 7 doublet and Γ 8 quartet.…”
Section: B Thermal Expansion and The Crystalline-electric-field Schemementioning
confidence: 99%
“…For example, several previous studies have suggested that a lattice distortion occurs at T ≈ 6 K which results in a lowering of the cubic symmetry. 7,11,12 Specifically, inelastic neutron scattering data suggest that the J = 7/2 groundstate magnetic multiplet of the Yb is split by the CEF further than allowed for by cubic point symmetry, 7 and specific heat data show a feature at 6 K that cannot be described only by a simple Schottky-term. 12 In addition, electron spin resonance experiments on Er-doped YbBiPt suggest that slight distortions away from cubic symmetry occur in the vicinity of the rare-earth sites, 11 and measurements of the thermal expansion have shown that the thermal expansion coefficient changes sign close to 6 K. 5 In this paper, we present results from high-resolution, highenergy x-ray diffraction experiments on single-crystal samples of YbBiPt.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations